Prywatyzacja wykonania zadania ochrony przeciwpożarowej przez gminę - Paplicki, Mateusz; Chrobak, Paulina; Poniatowski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Under the influence of political factors, the state decides which public tasks it will carry out through its organs, which will be transferable to other entities of public authority or non-public entities. Government and local government implements many public tasks. In confrontation with emerging new problems to be solved, rapidly changing social reality and growing needs of society, these administrations are not able to perform all public tasks assumed on themselves. It seems, therefore, that the optimal solution for this phenomenon is to free themselves from performing these tasks by transferring them to private entities for execution.
Keywords: prywatyzacja zadania; ochrona przeciwpożarowa; ochotnicza straż pożarna